Too little or too much? Exploring the inverted U-shaped nexus between voluntary environmental, social and governance and corporate financial performance - Teng, Xiaodong; Ge, Yongbo; Wu, Kun-Shan; Chang, Bao-Guang; Kuo, Lopin; Zhang, Xinwen (Frontiers in Environmental Science, 2022)
This study aims to examine the nonlinear relationship between environmental, social and governance (ESG) and corporate financial performance (CFP) using Taiwan Stock Exchange (TSE) listed firms with ESG disclosure between 2005 and 2019. The pooled ordinary least square (OLS) regression estimation results indicate the ESG-CFP nexus is a nonlinear (inverted U-shaped pattern). Furthermore, the individual ESG pillars each have a different relationship with CFP. Both the environmental and social pillars have an inverted U-shaped relationship with CFP, whereas there is no significant relationship between the governance pillar and CFP. The concave nonlinear relationship also supports the tenets of the “too-much-of-a-good-thing” effect. This research confirms that TSE listed firms should identify the optimal ESG value (threshold point), where ESG costs and benefits balance, to maintain sustainable development and stakeholder engagement.